Speaker-invariant speech emotion recognition with domain adversarial training - Leow, Bryan Xuan Zhen (Nanyang Technological University, 2021)
Recent advances in technology have given birth to intelligent speech assistants such as Siri and Alexa. While these intelligent speech assistants can perform a myriad of tasks just from the end users’ voice command, they lack the capability to recognize human emotions when formulating a response — a feature that would promote more ingenious usage for such speech assistants. Since such a Speech Emotion Recognition (SER) system would be used by the general population, it is necessary to derive speaker-invariant representation for the SER system.